Hubungan Perburuhan dan Hukum Perburuhan - Hadi, Samsul (TSAQOFAH, 2021)
This study aims to describe the relationship between labor and labor law. The research used descriptive qualitative. Data collection techniques using observation, and document study. The results of the study (1) The term labor is very popular in the world of labor/employment, besides this term has been used for a long time even from the Dutch era also because the old laws and regulations (before Law No. 13 of 2003 concerning Manpower) used the term laborer. (2) The term labor law used to be called labor law which is a translation of arbeidsrechts, but both have different meanings in terms of substance. Employment Law is all legal arrangements relating to labor either before work, during or in an employment relationship, and after an employment relationship. (3) Employment relationship is a legal relationship carried out by at least two legal subjects, namely the entrepreneur and the worker/labourer regarding a job. (4) Islam as a religion of rahmatan lil alamen, is very concerned about workers. Islam is very concerned about human rights, even though he is a slave. The companions who had helped the Prophet sallallaahu 'alaihi wa sallam, both slaves and free people, were all satisfied with the good attitude he gave. This is an ideal portrait that can be used as an example of muamalah between employers and their assistants, between leaders and employees.